Do success rate, complications of transobturator tape procedure differ based on experienced surgeon or residents? - (:unkn) unknown (My University, 2019)
OBJECTIVES: To investigate the postoperative surgical complications and patient satisfaction with the outside-in transobturator tape (TOT) procedure performed by an experienced surgeon compared to those performed by residents in training. METHODS: Patients who received TOT surgery performed by a resident under supervision of a faculty were included in group 1 (n = 31) whereas, patients operated by the same faculty were included in group 2 (n = 26). Both groups were compared for demographic data, procedure results, satisfaction rates as well as intraoperative and early postoperative (urinary retention, vaginal erosion, dyspareunia, infection, abnormal discharge) complications. Statistical Package for Social Sciences for Windows was used for statistical analyses. For continuous variables Mann-Whitney U test and for categorical variables Chi-square, Fishers exact tests were used. RESULTS: Stress incontinence in groups 1 and 2 were either completely cured or improved in 87.1% and 84.6%, respectively. The question" Would you like to have an operation like this again?" was answered positively by 26 (83.9%) of patients in group 1 and by 22 (84.6%) in group 2. There was no significant difference between two groups for the complication rates occurred within 90-days period. However, there was a significantly higher groin pain persisting more than three weeks in group 1 (38.7%) compared to group 2 patients (7.7%). CONCLUSIONS: There was statistically significant increased groin pain in the early period in TOT procedures performed by the residents. However, the complications observed in both groups did not affect the success rate or patient satisfaction.
Keywords: Female; Humans; Treatment Outcome; Clinical Competence; Patient Satisfaction; Internship and Residency; Suburethral Slings; Urinary Incontinence, Stress; Urinary Retention; Complication; Stress urinary incontinence; Surgeons; Complicación; Incontinencia urinaria de esfuerzo; Malla transobturatriz; Residentes; Residents; Transobturator tape